2019
DOI: 10.1002/ppul.24244
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol and ipratropium by inhaler is superior to nebulizer in children with severe acute asthma exacerbation: Randomized clinical trial

Abstract: Introduction In moderate‐severe asthma exacerbation, salbutamol by inhaler (MDI) is superior to salbutamol delivered by nebulizer (NEB); however, to our knowledge, no studies in children with exclusively severe exacerbations were performed. Objective To compare the efficacy of salbutamol and ipratropium bromide by MDI versus by NEB in severe asthma exacerbations. Methods We performed a clinical trial enrolling 103 children (2‐14 years of age) with severe asthma exacerbations (defined by the Pulmonary Score ≥ 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 16 publications
0
35
0
3
Order By: Relevance
“…In addition, use of several diagnostic modalities, including lung function testing, fractional exhaled nitric oxide, or methacholine tests, is limited, along with therapeutic interventions, such as nebulized treatments. 16 However, many services have actively responded to these challenges, most often by "virtual" clinics or other telehealth appliances, which flourished in all medical specialties during the COVID-19 epidemic. 17 Clinicians consider such clinics suboptimal, nonetheless adequate for the, hopefully, short time period under lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, use of several diagnostic modalities, including lung function testing, fractional exhaled nitric oxide, or methacholine tests, is limited, along with therapeutic interventions, such as nebulized treatments. 16 However, many services have actively responded to these challenges, most often by "virtual" clinics or other telehealth appliances, which flourished in all medical specialties during the COVID-19 epidemic. 17 Clinicians consider such clinics suboptimal, nonetheless adequate for the, hopefully, short time period under lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Initiative for Asthma (GINA) recommends avoiding the use of nebulizers due to the increased risk of disseminating COVID-19 to other patients and healthcare staff; they thus recommend the use of pressurized metered dose inhalers (pMDI) as the preferred delivery system during asthma attacks [43]. A recent randomized controlled trial (RCT) [44] showed that even in children with severe asthma exacerbations, administration of albuterol/salbutamol and ipratropium by MDI with valved-holding chamber and mask along with oxygen by nasal cannula was more effective than nebulized administration. GINA[43] and the British Thoracic Society[45] do not recommend stopping oral steroids in the patients already taking them for asthma management, and they do not recommend avoiding them for acute asthma attacks even if due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses help in choosing the method of treatment of a given disease -which one is most costeffective while maintaining the highest clinical effective-ness. Research to date has shown that SABA as well as the combination of SABA and SAMA used in aerosol therapy of respiratory diseases may differ not only in the method of administration, but also in clinical effectiveness, safety and costs associated with their use in patients [3][4][5][6][7][8][9]. Research results indicate that regardless of the calculation method, the use of SABA with pMDI in combination with a valved holding chamber (VHC) instead of NEB is associated with a reduction in total costs in both the emergency department and the hospital ward [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%